Reconciling the Impossibility of Authoritative Normativity with the Phenomenology of Moral Truth: A Metaethical Constructivist Solution - Ganiban, Claire E. (Tufts Archival Research Center, 2022)
In this thesis, I examine two competing theses about the nature of moral judgments that appear to be incompatible. First, that we purport to express truths when we make moral judgments and that this experience is veridical. Second, that authoritative normativity, or objective moral truths that ground non-contingent moral obligations, is impossible. I argue that a successful metaethical account of moral judgments must jointly affirm both theses. I diagnose why they seems incompatible, and I develop a metaethical constructivist position that reconciles them.; Thesis (B.A.)--Tufts University, 2022.; Submitted to the Dept. of Philosophy.; Advisor: Monica Kim.